Microcirculation of the gastric mucosa and the efficiency of standard eradication therapy in patients with duodenal peptic ulcer - Akermi, Jafar (Zaporozhye Medical Journal, 2013)
Purpose: explore the features of the condition of the gastric mucosa in patients with duodenal ulcer in the background of the standard triple therapy. Materials and мethods: we examined 68 patients with moderate and severe chronic duodenal ulcer. Among them, 35 were men and 33 - women. The patients' ages ranged from 22 to 64 years (the average age was 43,2 ± 6,3 years). The control group consisted of 25 healthy middle-aged persons who were examined by routine inspection. The study included only patients with H. pylori - positive duodenal ulcers. Method of study of the regional perfusion was laser doppler flowmetry (LDF) by «LАКК – 02» (NPP "Lazma", Russia). After an initial examination, all patients with H. pylori-associated duodenal ulcer were divided into two groups. Group I included 34 patients who received first-line eradication therapy for 7 days. The II group included 34 patients with duodenal ulcer who received first-line eradication therapy for 14 days. Therapy consisted of a proton pump inhibitor - rabeprazole (20 mg 2 times a day) and two antibiotic drugs: clarithromycin (500 mg 2 times a day), amoxicillin (1 g, 2 times a day for 7 or 14 days), pre - and probiotics. All patients were conducted esophagogastroduodenoscopy (EFGD) with biopsy in the ulcer twice at an interval of one month. The results of the study. The clinical manifestations of peptic ulcer disease was completely arrest in 27 (79,4%) of 34 patients from I group and in 30 (88,2%) of 34 patients from II group. Pain and dyspeptic syndromes were absent in all patients by the time the control EFGD (1 month). Eradication on 7th day of the treatment was reached in 72,3% of cases (24 patients). More effective was the 14-day treatment, the percentage of eradication during which amounted to 92,4% in the second group (32 patients). As for the microcirculatory changes, all patients showed a trend toward normalization of microcirculation after 1 month, the most pronounced changes were recorded in the 2nd group of patients. More pronounced changes in the microcirculation after 3 months of therapy also were recorded in the 2nd group. The analysis showed a dependence of the results of the duodenal ulcer treatment from duration of eradication therapy. Complete reduction of inflammatory changes of the stomach was achieved in 23,3% of patients who received 7-day eradication therapy, and significantly higher (P <0.05) - in patients with duodenal ulcer treated with a 14-day eradication therapy (46,4%). Consequently, a chronic inflammation of the mucous membrane of the stomach does not disappear with the elimination of the pathogen, “ex-Helicobacter pylori gastritis" and the risk of recurrence of clinical symptoms remains at 76,6% of elderly patients after a 7-day regimen and 53,4% of patients after a 14-day infection eradication schemes. Conclusions: The first-line eradication therapy (7 and 14-day) was less effective in patients with severe microcirculatory changes in the indices. After the effective eradication of H. pylori normalization of microcirculation can be indicated after 3 months in all patients and it reflexes the efficacy of reparative processes. Key words: microcirculation, peptic ulcer, duodenum, eradication therapy.